2004
DOI: 10.1111/j.1442-2050.2004.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic duct injury during esophagectomy: 20 years experience at a tertiary care center in a developing country

Abstract: Thoracic duct injury is an uncommon complication of esophagectomy. Experience in managing these cases is limited to large centers performing esophagectomies in good numbers. We analyzed the prospectively maintained esophageal diseases database of patients presenting to a surgical unit between 1982 and 2002. Among 552 esophagectomies during this period we had encountered 14 cases of chylothorax (2.54%). We analyzed the type and site of lesion and the impact of neoadjuvant therapy on the incidence of thoracic du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 29 publications
(54 reference statements)
5
45
2
Order By: Relevance
“…A similar finding was reported by Rao et al who found that the incidence of chylothorax in middle-third lesions was relatively higher than that in lower-third lesions (14). Thus, it is believed that the thoracic duct is in close proximity to the middle third of the thoracic esophagus, thus making it prone to injury during mediastinal dissection despite the surgeon's vigilance.…”
Section: Discussionsupporting
confidence: 80%
“…A similar finding was reported by Rao et al who found that the incidence of chylothorax in middle-third lesions was relatively higher than that in lower-third lesions (14). Thus, it is believed that the thoracic duct is in close proximity to the middle third of the thoracic esophagus, thus making it prone to injury during mediastinal dissection despite the surgeon's vigilance.…”
Section: Discussionsupporting
confidence: 80%
“…As for the increasing incidence for postoperative chylothorax after video-assisted thoracoscopic esophagectomy in our series, we presumed that the more keen-dissection during esophageal resection might be the potential reason. Although there is no conclusive data available regarding the indication and time point of surgical ligation of the thoracic duct, many authors still recommend early surgical ligation of the thoracic duct for minimizing the risk of mortality [3,8,12,21,22]. In our series, there were eight total patients who developed a chylothorax after videoassisted thoracoscopic esophagectomy.…”
Section: Discussionmentioning
confidence: 81%
“…Chylothorax after esophagectomy is a rare but potentially fatal complication which have been reported 0.4% -4% (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…If chyle is not stopped, patients will faced immune deficiency, resulting in infection and mortality (35). Some studies have shown the superiority of surgery over conservative treatment (34,(38)(39)(40). Thus, the treatment method of Chylothorax is conservative but when the outlet of the chest tube is more than 800 cc per day and it will continue for 4 to 5 consecutive days, waiting for stopping the leak may be dangerous due to leukopenia and malnutrition; therefore, surgery is required in these circumstances.…”
Section: Discussionmentioning
confidence: 99%